Scientific and Methodological Aspects of Studying the Interpretation of Justice in the Moral Views of Abu - Boymirzayev Hasanboyevich (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
The article explores the scientific and methodological foundations of studying the interpretation of justice in the moral views of Abu Abdullah Rudaki, considering the historical, socio-cultural conditions, and social environment of the Muslim East. Additionally, the scientific and methodological aspects of studying the interpretation of justice in Rudaki’s moral views are analyzed.